Simulación y diseño de un sensor acústico piezoeléctrico para detección de partículas. - Campo-Valera, María; Ardid Ramírez, Miguel; Felis-Enguix, Iván; Martínez Mora, Juan Antonio (My University, 2017)
Bubble chambers used in detectors for detecting dark matter use piezoelectric sensors in order to detect and discriminate the acoustic signals from bubbles growth in the superheated liquid when a particle interaction occurs. The Research Group in Applied Acoustics to Astroparticles Detection from UPV developed a particle detector, whose acoustic sensors are attached to the outer walls of the chamber. In order to optimize the operation of the sensor, both analytical and numerical models are developed, as well as experimental tests for characterization of sensors design were performed. The results of these studies allows a particular design criterion for the construction of such sensor for future dark matter bubble chamber detectors.
Keywords: Acústica; Detectores; Piezoelectricidad; Materia oscura (Astronomía); Cámaras de burbujas; Piezoelectricidad; Sensores acústicos; Materia oscura; Simulaciones FEM